Effects of hydroalcoholic, methanolic, and hexane extracts of brown algae Sargassum angustifolium on scopolamine-induced memory impairment and learning deficit in rodents - Azin Hassanzadeh; Afsaneh Yegdaneh; Mohammad Rabbani (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Properties of Alzheimer's disease, can be caused by several reasons and there is no definite treatment for it. We aimed to study the effect of the hydroalcoholic extract, methanolic and n-hexane fractions of brown algae Sargassum angustifolium on memory impairment in mice and rats. Experimental approach: Hydroalcoholic extract (25, 50, 100, 200 mg/kg), methanolic (20 and 40 mg/kg) and n-hexane (40 and 60 mg/kg) fractions of S. angustifolium were administered for 21 days intraperitoneally before scopolamine injection (2 mg/kg) on day 21. Rivastigmine was administered for 3 weeks intraperitoneally as well. Then, cognitive function was evaluated by three behavioral tests: passive avoidance, object recognition, and the Morris Water Maze test. Findings/Results: Scopolamine induced memory impairment and rivastigmine significantly reversed the memory dysfunction in all three tests. Hydroalcoholic extract and methanolic fraction significantly reversed scopolamine-induced memory impairment in passive avoidance by 64% and 55% and enhanced the recognition index in the object recognition test. In the Morris water maze test probe trial and training session, on days 3 and 4, the hydroalcoholic extract showed a significant decrease in time spent in the target quadrant and path length, respectively. Also, hydroalcoholic extract and methanolic fraction decreased escape latency time in training sessions on days 3 and 4, by 50% and 31% in comparison to scopolamine. N-hexane fractions had no significant effect on scopolamine-induced cognitive impairment. Conclusion and implications: Although the n-hexane fraction wasn't effective, the administration of hydroalcoholic extract and the methanolic fraction of S. angustifolium enhanced scopolamine-induced memory impairment.